Epistemic Disobedience and Decolonial Healing in Norma Elía Cantú’s Canícula - Poks, Małgorzata (Studia Anglica Posnaniensia, 2016)
Using the U.S.-Mexican border as the place of enunciation, Cantú’s autoethnobiographical novel insists on the materiality of the border, especially for those living on its southern side, while simultaneously deconstructing it as artificial - a line splitting families and assigning nationalities on an arbitrary basis. Being a collage of photographs from the time the writer was growing up in southern Texas and the cuentos inspired by these visuals, Cantú’s Canícula documents how border crossings and re-crossings become symptomatic of living in a liminal space and how they destabilize the concept of nationality as bi-national families must learn to live with ambiguity. On the one hand, there is the undeniable materiality of the border, with its pain, fear, deportations, and other discriminatory practices; on the other, there is a growing border community of resistance cultivating the memory that they are not immigrants, that they lived in Texas before the Guadalupe-Hidalgo treaty. The paper examines the community’s strategies of survival in the contested cultural and social space and advances the thesis that, giving her community an awareness of its homogeneity and reclaiming its place within the larger socio-political context, Cantú becomes an agent of empowerment and change. She helps decolonize knowledge and being.